Wisdom as moderate scepsis changes over the life-span - Brugman, Gerard M. (1997)
Wisdom is analyzed in terms of the Greek sceptic tradition. Crucial for wisdom is the acknowledgment of the inability to acquire infallible knowledge and the acceptance to act upon the world on the basis of that same fallible knowledge. This fallibilism is based on the notion of the plausible. This fallibilistic epistemology is useful in the domain of life pragmatics, notably a domain of ill-defined problems. 1 t is assumed that the nature of wisdom is a function of culture and history: first as a content and then to a more cognitive style concept. This means that wisdom has historically evolved from a cognitive toa metacognitive capacity. With respect to changes in wisdom over the life span it is argued that in contrast to the communis opinio, these changes are not age-related. Finally, it is assumed that changes in wisdom are a function of dealing with life-events, the accumulation of knowledge, cognitive development and personality.